Second-Look Colonoscopies and the Impact on Capacity in FIT-Based Colorectal Cancer Screening - Grobbee, E.; Kapidzic, A.; van Vuuren, A.; van Leerdam, M.; Lansdorp-Vogelaar, Iris; Looman, C.; Bruno, M.; Kuipers, E.; Spaander, M. (Nature Publishing Group, 2015)
Objectives: Fecal immunochemical testing (FIT) and colonoscopy are tandem procedures in colorectal cancer (CRC) screening. A positive FIT predicts advanced neoplasia (AN) that requires endoscopic detection and removal. En bloc or piecemeal resection of AN is associated with a significant rate of residual or recurrent neoplasia. Second-look colonoscopies are indicated to assess completeness of removal of AN. These colonoscopies can make a substantial demand on colonoscopy capacity and health-care system. This study is the first to evaluate the demand and risk factors for second-look colonoscopy in FIT CRC screening. Methods: All colonoscopies after a positive FIT, in subjects aged 50–74 years approached for 3 rounds of FIT screening, were prospectively registered. Second-look colonoscopies were defined as any colonoscopy within 1 year following a colonoscopy after positive FIT. Results: Out of 1,215 FIT-positive screenees undergoing colonoscopy, 105 (8.6%) patients underwent a second-look colonoscopy, of whom 30 (2.5%) underwent more than one colonoscopy (range 2–9), leading to a total of 149 (12.3%) additional colonoscopies. Main reasons for second-look colonoscopies were assessment of complete AN removal (41.9%) and need for additional polypectomy (34.3%). Risk factors were advanced adenomas and poor bowel preparation (P<0.001). High fecal hemoglobin concentration was the only predictor of a second-look colonoscopy before index colonoscopy (P<0.001). Conclusions: Second-look colonoscopies have substantial impact on colonoscopy resources, increasing the demand with 12%. The main reasons for these second-look colonoscopies were previous incomplete polypectomy and control of completeness of removal of neoplastic lesions. A high fecal hemoglobin concentration as measured by FIT can help to identify patients at risk of a second-look colonoscopy.